Smart Village Masterplan in Samida Tourism Village, Garut District Using Ward and Peppard Framework Method - Sopiyan, Deni; Prasetyo, Hadi; Firmansyah, Hendra Sanddi (LPPM STMIK Mardira Indonesia, 2024)
The Samida Tourism Village in Garut Regency has rich natural and cultural potential, including the creative bamboo crafts produced by local artisans, which include household items and accessories made from bamboo. It provides several educational tourist packages, including bamboo tourism, planting education, rice field plowing education, and fish farming education, along with lodging alternatives such as homestays, villas, camping sites, and glamping. Moreover, it includes swimming pool tourism, outbound activities, and cafés. Nonetheless, these resources have yet to be adequately optimized. Comprehensive planning through a Smart Village Master Plan is essential to improve competitiveness and the quality of tourism services. This study will develop a Smart Village Master Plan for the Samida Tourism Village utilizing the Ward and Peppard Framework, which is recognized for its strategic planning in Information Systems and Information Technology (IS/IT). The Ward and Peppard Framework offers a structured methodology synthesizing business environment analysis, business strategy, and IT strategy to guarantee coherence between business goals and IT expenditures. The implications of this research provide a strategic guide for designing and implementing a smart village masterplan that leverages natural and cultural potential, such as bamboo crafts and educational tourism packages. The application of the Ward and Peppard method is expected to create synergy between business objectives and IT expenditures, thereby enhancing the efficiency of tourism services.